REPRESENTATION OF IHSAN BEHAVIOR IN KAMBING DAN HUJAN NOVELS BY MAHFUD IKHWAN - Abdul Karim Wirawan (Jurusan Sastra Indonesia, 2019)
This paper tries to identify the Ihsan behavior contained in the Kambing dan Hujan novel by Mahfud Ikhwan. Ihsan behavior is identified from the behavior of charity, patience, jihad, and fear. This paper uses a qualitative approach to examine representations of Ihsan behavior in the Goat and Rain novels. The steps of data analysis in this paper are divided into six specific stages, namely (1) processing and preparing data for the analysis process, (2) reading the entire data to find general meaning, (3) initiating data codification, (4) applying coding to describe the domains, participants, categories, and themes analyzed, (5) presentation of descriptions and themes in the form of narratives, and (6) making interpretations.